Resistance Mechanisms to Antimicrobial Peptides in Gram-Positive Bacteria - Assoni, Lucas; Milani, Barbara; Carvalho, Marianna Ribeiro; Nepomuceno, Lucas Natanael; Waz, Natalha Tedeschi; Guerra, Maria Eduarda Souza; Converso, Thiago Rojas; Darrieux, Michelle (Frontiers in Microbiology, 2020)
With the alarming increase in pathogenic multidrug resistant bacteria over the last decades, antimicrobial peptides (AMPs) have been investigated as a potential treatment for those infections, directly through their lytic effect or indirectly, due to their ability to modulate the immune system. There are still concerns regarding the use of such molecules in the treatment of infections, however various concepts are being tested to reduce the potential complications. Human defense peptides consist of an important part of the innate immune system, against a myriad of potential aggressors, which have in turn developed different ways to overcome the AMPs microbicidal activities. Since the antimicrobial activity of AMPs vary between Gram-positive and Gram-negative species, so do the bacterial resistance arsenal. This review discusses the mechanisms exploited by Gram-positive bacteria to circumvent killing by antimicrobial peptides. Specifically, the most clinically relevant genera, Streptococcus spp, Staphylococcus spp, Enterococcus spp and Gram-positive bacilli, have been explored.